2010
DOI: 10.1590/s0103-21002010000200012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da dor em pós-operatório de cirurgia cardíaca

Abstract: Objectives: To evaluate the intensity of pain in patients after cardiac surgery; the study aimed to: 1-identify possible associations between physiological alterations (tachycardia, tachypnea, increased blood pressure, sweating, paleness, nausea and vomiting) and postoperative pain, and 2-describe the used analgesia. Methods: This prospective study evaluated 30 patients in a public teaching hospital, from the immediately postoperative period till the 4th postoperative day. To analyze the data was used the soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
1
9
0
11
Order By: Relevance
“…Conversely, a different study has shown that from the immediate postoperative period (IPO) to the fourth postoperative day, there have been 344 analgesic prescriptions, being 127 (36.9%) simple analgesics, 120 (34.9%) opioids and 97 (28.2%) NSAIDS. It is worth stressing that most drugs (52.65) were under the "medical criteria" schedule 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a different study has shown that from the immediate postoperative period (IPO) to the fourth postoperative day, there have been 344 analgesic prescriptions, being 127 (36.9%) simple analgesics, 120 (34.9%) opioids and 97 (28.2%) NSAIDS. It is worth stressing that most drugs (52.65) were under the "medical criteria" schedule 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A angina advinda da DAC juntamente com os sentimentos desencadeados pela expectativa à CRVM podem influenciar nos aspectos físicos e emocionais do paciente interferindo possivelmente na qualidade de vida [25][26][27] . O domínio dor, um dos aspectos avaliados no questionário de qualidade de vida aplicado no presente estudo foi o que apresentou em sua melhora, uma maior diferença entre os scores pontuados nas avaliações.…”
Section: Discussionunclassified
“…Pain is expected or acceptable for some people and not for other people. (22) This expectation influences the assessment of pain because each individual's painful experience is influenced by the subject's personal history, understanding of pain and mental status. Different people under similar or identical conditions may experience pain in completely different manners.…”
Section: Discussionmentioning
confidence: 99%